Pengaruh Kompensasi dan Kepuasan Kerja terhadap Kinerja Dosen di Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta - Rinduan Zain; Anaas Tri Ridlo Dina Yuliana (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
Quantitative research of the correlation studies with model aims to analyse the influence of large contributions and relations variables (X1) compensation and job satisfaction (X2) against a variable performance lecturer (Y) when controlled with variable organizational commitment (Z) and basing on the theory of two factors that was conceived by Frederick Herzberg. The results of the comparison between the coefficients of correlation bivariat (X1 = Y = compensation and performance Lecturer) and partial correlation coefficients (X1 = compensation, organizational commitment and Z = Y = performance Lecturer) indicate that ryx1 > ryx1z i.e. 0317 > 0268. This means that the compensation effect on performance because the lecturer is mediated by the commitment of the organization. The regression results to prove the value of the β1 = β2 = 0153 and 0383, where compensation contributions and commitments of the Organization was able to improve the performance of lecturers of 54%. That is, when a lecturer at Faculty of Tarbiyah UIN Sunan Kalijaga Pedagogy and has compensation and high organizational commitment can enhance the performance of lecturers of 54%. While on the job satisfaction variables retrieved results correlation bivariat (X2 = job satisfaction with Y = performance Lecturer) significant i.e. 0.001 < α 0.10, while partial correlation results (X2 = job satisfaction, organizational commitment, Z = and Y = performance lecturer) was not significant because significant numbers 0086 > α 0.10, so that job satisfaction is really in a linear effect on the performance of a lecturer. The results of the regression coefficient regression proved the job satisfaction (β) of 0267, where the contribution of job satisfaction was able to increase the performance of a lecturer of 27%. That is, when a lecturer at the Faculty of pedagogy and Tarbiyah UIN Sunan Kalijaga Yogyakarta has a high job satisfaction though have no organizational commitment can enhance the performance of lecturers of 27%.